Assessment of Turkey's energy management performance via a hybrid multi-criteria decision-making methodology - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Energy has been the major input for the national economies. While fossil-based energy resources are diminishing, researchers are focusing on alternative fuels and various technology options for conversion, distribution, and end user's operating environment processes. As the search for the alternative pathways for the sustainable economy idea continues, management factor is getting considerably important within each phase of energy generation and consumption. In this paper, we employ a hybrid multi-criteria decision-making methodology to evaluate the energy management performance of selected nine countries with a focus on Turkey with respect to a number of criteria. The hybrid approach integrates three methods, viz. Analytical Hierarchy Process, Multi-Criteria Optimization and Compromise Solution, and Technique for Order Preference by Similarity to Ideal Solution. It enables decision-makers assess multiple alternatives within an analytic framework while considering multiple criteria simultaneously. We perform our analysis for each year between 2001 and 2016. The results show that, with its fast-growing population, dynamic economy, and huge energy saving potential, Turkey displays a low profile compared to the other countries in our scope. Our results can be encompassed by in-depth analyses and long-term plans to shift the country's energy technology selection strategies to more efficient, cost-effective and cleaner options. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Energy management; Energy policy; Multi-criteria decision-making; Analytic hierarchy process; TOPSIS; VIKOR; Goal programming; HIERARCHY PROCESS; CONSUMPTION; SELECTION; MODEL; CRITERIA; POLICY; SYSTEMS; SECTOR; VIKOR; IRAN